The Unintended Impact of R&D Tax Credits on Innovative Search - Balsmeier, Benjamin; Fleming, Lee; Stiebale, Joel; Veihl, Maria (The Review of Economics and Statistics, 2024)
Abstract Research and development tax credits often aim to increase investment in experimentation, hoping that firms invent fundamentally new technologies that in turn generate positive spillovers. Since most policies require that companies make profits in order to claim credits, they might also shift investments towards less risky refinement and exploitation. Following the availability of credits, we demonstrate that firms do not experiment but deepen invention in areas of extant expertise. We observe stronger shifts for firms operating in uncertain markets where search failures are more likely to reduce credit eligibility.